Eye donation: awareness, knowledge and willingness among general public in Southern Indian population - Pallerla, Srinivasa Reddy; Khanna, Rohit C.; Krishnaiah, S.; Keeffe, Jill (International Journal Of Community Medicine And Public Health, 2022)
Background: Aim of the study was to assess the awareness, knowledge and willingness to donate eyes among general public in southern Indian states of Andhra Pradesh and Telangana. Methods: A cross sectional population-based survey used a semi structured questionnaire on awareness, knowledge and willingness for eye donation. Stratified multistage cluster random sampling method was used with a sample size of 867 adults >16 years based on, estimated awareness of cataract 70%, assuming an expected rate of 85%, design effect of 1.5, margin of error 4% with 95% confidence interval with 25% from urban areas and 75% from rural areas. Having heard of eye donation was defined as awareness and having knowledge of the ideal time to donate the eyes was considered as knowledge. A pilot study was conducted to validate the questions used in the main study. Statistical package SPSS (version 19) was used for analysis to calculate logistic regression and odds ratios for gender, age, education and urban-rural areas. Results: A total of 782/867 (90.1%) subjects participated in the survey with females 47.4%. 603 subjects (77.1%) were aware of eye donation. 301 subjects (38.5%) were willing to donate eyes. The 297 subjects (49.3%) were aware of the ideal time for donation after death. Conclusions: Awareness of eye donation was high among the general public but the willingness to donate eyes was poor. There is a need to identify barriers for eye donation to increase the voluntary donation of the eyes to combat corneal blindness.